The Influence of Dairy Farming Motivation on Dairy Cows Productivity in Different Disaster Prone Areas of Merapi Volcano - Andarwati, Siti (2015)
This study aimed to analyze: 1) Dairy farmers motivation in disaster-prone areas (DPA) II and DPA III of Merapi volcano, and 2) The influence of dairy farmers motivation on dairy cows productivity. The research was conducted using household survey with interviews involving respondents were selected. The location determined by purposive sampling study, which was located in DPA II and DPA III of Merapi volcano. Samples or materials research was determined by Purposive Sampling method. Dairy farmers in disaster-prone areas chosen with the following criteria: 1) maintain dairy cows at least one year, and 2) as the member of farmer group’s cage. The respondent took by using the Census for farmers who have the criteria. Assessment of dairy farming motivation was based on criteria according to the Likert scale. In order to determine the influence of dairy farming motivation on the productivity of dairy cows made by Regression. The average value of dairy farming motivation was high for both areas of research in DPA III of 110.19 while in DPA II amounted to 106.05. Farmer motivation in the DPA III was higher if compared with the farmer in DPA II. There were very little influence of dairy farming motivation on the productivity of dairy cows, even in terms of milk production (0.07), services per conception (0.05) and calving interval (0.002).